Vibronic emissions between the a1Σ+, b1Π, c1Δ, d1Σ+, e1Σ−, and f1Π states of the diatomic silicon carbide SiC. (August 2019) - Zhang, Meng; Wang, Kedong
Highlights: Radiative lifetimes are of the order of 10 −6 s for the d 1 Σ + and f 1 Π states. d 1 Σ + –b 1 Π and f 1 Π–b 1 Π transitions are strong. Radiative lifetimes are of the order of 10 −3 s for the e 1 Σ − state. Vibronic emissions of the f 1 Π–a 1 Σ + system are very weak. Radiative lifetimes are approximately 10 −3 –10 −4 s for the b 1 Π and c 1 Δ states. Abstract: In recent years, emissions of silicon carbide molecule have been widely detected in carbon stars, stellar atmospheres, and interstellar molecular clouds. In order to evaluate the vibronic transitions between different singlet states of this molecule, we calculate the potential energy curves of the a 1 Σ +, b 1 Π, c 1 Δ, d 1 Σ +, e 1 Σ −, and f 1 Π states and compute the transition dipole moments between them. The band origins, Einstein A coefficients, and Franck–Condon factors of the vibronic emissions are computed for all possible transitions between these six lowest-lying states. Of these vibronic transitions, only the emissions of the d 1 Σ + –b 1 Π and f 1 Π–b 1 Π systems are strong. The emissions of the f 1 Π–a 1 Σ + system are so weak that it is very difficult to measure them through spectroscopy. The rotationless radiative lifetimes are approximately several microseconds for all vibrational levels of the d 1 Σ + and f 1 Π states, indicating that the vibronic emissions originating from the two states occur easily. The rotationless radiative lifetimes are approximately several ms for all vibrational levels of the e 1 Σ − state. Based on the Einstein A coefficients, we conclude that it is difficult to measure these emissions generated from the e 1 Σ − state, regardless of the radiative lifetime. The rotationless radiative lifetimes are of the order of 10 −3 –10 −4 s for all vibrational levels of the b 1 Π and c 1 Δ states. The transition probabilities reported in this study can be employed to explain why the emissions between the singlet states of this molecule have rarely been measured to date, both in a spectroscopy experiment and in outer space. Graphical abstract: In recent years, emissions of SiC molecule have been widely detected in carbon stars, stellar atmospheres, and interstellar molecular clouds. To evaluate the vibronic transitions between different states of this molecule, this paper calculates the potential energy curves, spectroscopic parameters, transition dipole moments, and transition probabilities of the a 1 Σ +, b 1 Π, c 1 Δ, d 1 Σ +, e 1 Σ −, and f 1 Π states of the SiC molecule. The rotationless radiative lifetimes are approximately 10 −3 s for the e 1 Σ − state, 10 −3 –10 −4 s for the b 1 Π and c 1 Δ states, and 10 −6 s for the d 1 Σ + and f 1 Π states. Overall, the d 1 Σ + –b 1 Π and f 1 Π–b 1 Π transitions are strong; the b 1 Π–a 1 Σ +, c 1 Δ–b 1 Π, d 1 Σ + –a 1 Σ +, e 1 Σ − – b 1 Π, f 1 Π–c 1 Δ, f 1 Π–d 1 Σ +, and f 1 Π–e 1 Σ − transitions are weak; the f 1 Π–a 1 Σ + transition is so weak that it is difficult to measure in a spectroscopy experimentImage, graphical abstract .